Aberrant evoked calcium signaling and nAChR cluster morphology in a SOD1 D90A hiPSC-derived neuromuscular model - Couturier, Nathalie; Hörner, Sarah Janice; Nürnberg, Elina; Joazeiro, Claudio; Hafner, Mathias; Rudolf, Rüdiger (Frontiers in Cell and Developmental Biology, 2024)
Familial amyotrophic lateral sclerosis (ALS) is a progressive neuromuscular disorder that is due to mutations in one of several target genes, including SOD1. So far, clinical records, rodent studies, and in vitro models have yielded arguments for either a primary motor neuron disease, or a pleiotropic pathogenesis of ALS. While mouse models lack the human origin, in vitro models using human induced pluripotent stem cells (hiPSC) have been recently developed for addressing ALS pathogenesis. In spite of improvements regarding the generation of muscle cells from hiPSC, the degree of maturation of muscle cells resulting from these protocols has remained limited. To fill these shortcomings, we here present a new protocol for an enhanced myotube differentiation from hiPSC with the option of further maturation upon coculture with hiPSC-derived motor neurons. The described model is the first to yield a combination of key myogenic maturation features that are consistent sarcomeric organization in association with complex nAChR clusters in myotubes derived from control hiPSC. In this model, myotubes derived from hiPSC carrying the SOD1 D90A mutation had reduced expression of myogenic markers, lack of sarcomeres, morphologically different nAChR clusters, and an altered nAChRdependent Ca 2+ response compared to control myotubes. Notably, trophic support provided by control hiPSC-derived motor neurons reduced nAChR cluster differences between control and SOD1 D90A myotubes. In summary, a novel hiPSC-derived neuromuscular model yields evidence for both muscleintrinsic and nerve-dependent aspects of neuromuscular dysfunction in SOD1-based ALS.